Hubungan Antara Higienitas Helm dengan Pertumbuhan Jamur Dermatofita pada Helm Pengemudi Ojek di Kawasan Wisata Religi - Wahyu Ari Setiyawan; Indanah; Navira Septiana Ulfa (Poltekkes Kemenkes Semarang, 2026)
Dermatophyte fungal infections are one of the most common contagious skin diseases in the community, especially on the scalp, hair, and nails. Transmission can occur indirectly through objects, one of which is helmets. Motorcycle taxi drivers in tourist areas are at high risk of fungal contamination due to the massive use of helmets. This study aims to determine the relationship between helmet hygiene levels and dermatophyte fungal growth on motorcycle taxi driver helmets in religious tourist areas. The type of research used is observational analytical with a cross-sectional approach. The research sample consisted of 37 motorcycle taxi drivers selected using purposive sampling. Helmet hygiene data was obtained through a questionnaire, which found that most respondents had good hygiene (78.4%) and 8 respondents (21.6%) had poor hygiene. The results of dermatophyte fungal growth were tested using culture on SDA medium, revealing that the majority of samples were negative (30 respondents, 81.1%), while 7 samples were positive for dermatophytes (18.9%) from the genera Microsporum sp. and Trichophyton sp., using LPCB staining. Data analysis was performed univariately and bivariately using Fisher's Exact test. The results of Fisher's Exact test showed a significant relationship between helmet hygiene and dermatophyte fungal growth (p < 0.001) with an odds ratio of 84.000. The conclusion of this study indicates that poor helmet hygiene can increase the risk of dermatophyte fungal contamination, which causes tinea capitis, in religious tour motorcycle taxi drivers.